Public Relations Campaign Program Evaluation: A Descriptive Study of the 'Hard Work Free of Worry' Campaign by BPJS Employment - Darmawan, Java Chandra; Wardasari, Nilam (Advances in Social Sciences Research Journal, 2024)
This research discusses the evaluation of the public relations campaign "Kerja Keras Bebas Cemas" launched by BPJS Ketenagakerjaan to raise awareness and participation among the public, particularly informal workers, in the social security program. The purpose of this research is to evaluate the implementation stages, effects, and impacts of the campaign. This research employs a descriptive qualitative method involving in-depth interviews, documentation, and online observation to gather data. The evaluation results indicate that the campaign successfully raised public awareness and participation, as evidenced by a significant increase in participant registrations. The campaign was conducted on a national scale, led by the Deputi Bidang Komunikasi and executed integrally by all BPJS Ketenagakerjaan branch offices through systematic stages. The conclusion of this research shows that the "Kerja Keras Bebas Cemas" campaign effectively achieved its goals of increasing participation and public awareness. However, improvements are needed in message measurement and media selection to enhance effectiveness further.